Lucid - Lokman, Nursabrina Muhamad (Nanyang Technological University, 2023)
LUCID is a 2D-animated graphic novel about two main characters, Sam and Izzy, who end up trapped in the realm of spirits, the Pasar Malam, after an attempt to achieve lucid dreaming goes wrong. This graphic novel is firstly: an exploration of animated graphic novels as a format for creative media, and secondly: an attempt to successfully execute a locally-inspired cerita hantu, or ghost story. This report is intended as a reflection of the project’s development from the initial stages of inspiration to its final form.